DYNAMIC MODEL AND FUZZY-PD TYPE CONTROL OF FOUR-LEGGED QUADRUPEDAL ROBOT WITH A PRONKING GAIT - Soyguder, Servet; Alli, Hasan (World Scientific Publ Co Pte Ltd, 2010)
In this study, dynamic model, simulation and control of a four-legged quadrupedal robot have been performed for a pronking gait. To obtain the numerical simulation of the system with pronking gait, the different dynamic structures have been solved in a sequential closed loop (stance, flight phase). Spring Loaded Inverted Pendulum (SLIP) has been used as a dynamic model to simplify the simulation of the system and ease to understand the pronking gait. In addition, the quadrupedal robot with pronking gait has been controlled by fuzzy PD-type control algorithm. The number of the performed control action during the phases of pronking gait in this study is smaller than those of the studies in the literature. Consequently, the proposed improvements in this study make both the system control easy and the system performance increase by decreasing the run time for each loop.
12th International Conference on Climbing and Walking Robots the Support Technologies for Mobile Machines (CLAWAR) -- SEP 09-11, 2009 -- Istanbul, TURKEY